PROPOSED PRE-MARITAL PROGRAM CURRICULUM (STUDY AT RELIGIOUS AFFAIRS OFFICE, DUREN SAWIT JAKARTA) - Meni Budiarti; Didin Hafidhuddin; Ibdalsyah Ibdalsyah (Program Studi Magister Pendidikan Agama Islam, Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2018)
The purpose of marriage is to get happiness; but apparently not all marriages succeed. Some couples struggle the married problems, such as domestic violence for women and children, financial problems, having unfair polygamy, irresponsible husband or wife, and so on. Some of these problems lead to divorce which the number is increasing rapidly. We need to aware of this matter. If there's no correct action, it will more increase and it would impact to national defense. Religious Affairs Office takes part to this matter by conducting pre-marital program to equip prospective husbands and wives with the basic knowledge of married life. This study identified how the implementation of pre-marital program which covered the duration of the program, the facilitator, the facilitation, and the most importance thing is the program material. The study referred to marital fiqih, the theory of sakinah family, husband and wives "adab", and the marital government regulation. The study is located at the Religious Affairs Office, in Duren Sawit, East of Jakarta. The method of the study is descriptive qualitative study. The result of this study is a pre-marital program improvement which will be a standard for Muslims couple entrance a marriage.   Keywords : Pre-Marital program, sakinah family, Religious Affairs Office